2023
DOI: 10.1364/ome.475309
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Bragg soliton dynamics for enhanced supercontinuum generation in ultra-silicon-rich-nitride devices [Invited]

Abstract: Bragg-soliton dynamics in a 2-stage ultra-silicon-rich-nitride (USRN) chip-based device, consisting of a cladding-apodized modulated Bragg grating (CMBG) stage and a USRN channel waveguide stage, is studied and optimized for enhanced supercontinuum generation. We observe that the enhancement is strongly dependent on the Bragg-soliton effect temporal compression developing in the CMBG stage, which is linked to both device and input pulse parameters. With the optimal parameter combination, a supercontinuum spann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Recently it has been reported that the USRN-waveguide is a promising platform to efficiently compress optical pulses and generating SC with significantly low optical power. 5,6 The similar optical pulse compression effect plays a critical role in MI dynamics that is central in long pulse SC generation.…”
Section: Theoretical Modelmentioning
confidence: 99%
“…Recently it has been reported that the USRN-waveguide is a promising platform to efficiently compress optical pulses and generating SC with significantly low optical power. 5,6 The similar optical pulse compression effect plays a critical role in MI dynamics that is central in long pulse SC generation.…”
Section: Theoretical Modelmentioning
confidence: 99%